(3eYGfj GdbQBf hEYQGHgs - (3GdRLGL , EHQGgje Hf GdSQj Hf Sgd, CHhESMGb,J (B311 (3g` s ((3HQgGf GdOjf GHf GdbhGS GdTgjQHGHf GdUGQe s)
(3ChdgG (B:s
(3jHJOF HChd ShQI eQje s
(3BNQgG (B:s
(3hjfJgi HBNQ ShQI aGWQ s
(3ef fSNI CNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B33s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B46 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1730s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(122) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs